Steady non-uniform extensional motions as applied to kinematic description of polymer fibre formation - Zahorski, S. (Archives of Mechanics, 1997)
It is shown that the concept of steady non-uniform extensional motions (NUEM) can be used for kinematic description of polymer fibre formation, taking into account the variable geometry and shearing effects. To this end, pretty general, materially non-uniform constitutive equations, depending on temperature distributions, structure formations, etc., are applied and the linearized perturbation procedure is developed. Especially simple expressions describing the additional velocity fields are obtained for the first order approximation.